STUDI PENGELOLAAN TAMAN HUTAN RAYA BUNG HATTA DI KOTA PADANG - Nurman, Retno Putra; Bakaruddin, Bakaruddin; Zuriyani, Elvi (Pendidikan Geografi, 2013)
Hutan Raya Bung Hatta park is natural area of forest ecosystem with the high bioldiversit. The beautiful scenery, such as valley,Â  the hill and in urban area in the low land area it is not regularly visit by the people in daily or holiday. The purposes of this research to get data, information and to analyze the management of Hutan Raya Bung Hatta park from aspects such as : 1) tourism, 2) education, and 3) the supporting cultivation. This research was using descriptive metod with, system approach to describe the management of Hutan Raya Bung Hatta park. The research is conducted in Hutan Raya Bung Hatta park, the researcher used Â purposive sampling tecnight to interview manager of the park, tourism, office the visitor Tman Hutan Raya Bung Hatta, Official tourism, the visitor forestry officer, Bapedalda as informants for the. The technique of analysis data used to data reduction, data presentation, and conclusion. The result of this research are 1). The management of Hutan Raya Bung Hatta park is run by forestry and torism office, the management of this place has maximum because of many weaknesses such as infrastructure, cleanness and security, 2). The park also have public education function for student and university 3). The park also supported the plant conservation. Of through plant nursery as well as plantatium.